FRAMING MEDIA ONLINE TERHADAP PEMBERITAAN MENGENAI SUSILO BAMBANG YUDHOYONO MENJELANG PEMILU LEGISLATIF 2014 (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2014)
AbstractThis study examines how the framing media done on  Susilo Bambang Yudhoyono (SBY), especially the framing is done by the online media. The research method uses Framing Analysis, particularly as developed by Gramsom and Modigliani. Media studied were www.kompas.com and www.inilah.com, which claim to represent as independent media. There are differences and similarities between the two media in framing the news about SBY:  www.inilah.com news about SBY such that SBY this suggest: 1) as of President, he failed in the duties; 2) as the head of government, the SBY was perceived impede the legal process; and 3) as chairman of the party, SBY  likely to commit fraud. While  www.kompas.com, SBY as President and head of government are fair, while as the chairman of the party, SBY  inclined to cheat. Keywords: media framing, Susilo Bambang Yudhoyono, online media